2022
DOI: 10.1186/s12894-022-01022-7
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings of retroperitoneal anastomosing hemangioma: a case report and literature review

Abstract: Background Anastomosing hemangioma is an uncommon benign vascular tumor that may be mistaken for a malignancy. The imaging findings of anastomosing hemangioma are not well provided from the previous reports. Herein, in the study, we discuss the imaging findings for one case of retroperitoneal anastomosing hemangioma. Case presentation One 64-year-old female patient had a left retroperitoneal mass that was incidentally detected upon physical examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…However, in the 4 cases of their study, only 1 case showed high signal on DWI with low signal on the ADC map; another patient exhibited slight hyperintensity on both DWI and ADC, which was consistent with the diffusion features of our cases and was likely due to the T2 shine-through effect rather than true restricted diffusion; ADC maps of the remaining 2 cases were not provided. In the case reported by Rogers et al , hepatic AH demonstrated no restricted diffusion ( 10 ), which is similar to a recently published case of retroperitoneal AH ( 15 ). In a previously published hepatic AH case at our hospital ( 14 ), the lesion showed no obviously restricted diffusion, with a mean an ADC value of 1.81×10 -3 mm 2 /s.…”
Section: Discussionsupporting
confidence: 86%
“…However, in the 4 cases of their study, only 1 case showed high signal on DWI with low signal on the ADC map; another patient exhibited slight hyperintensity on both DWI and ADC, which was consistent with the diffusion features of our cases and was likely due to the T2 shine-through effect rather than true restricted diffusion; ADC maps of the remaining 2 cases were not provided. In the case reported by Rogers et al , hepatic AH demonstrated no restricted diffusion ( 10 ), which is similar to a recently published case of retroperitoneal AH ( 15 ). In a previously published hepatic AH case at our hospital ( 14 ), the lesion showed no obviously restricted diffusion, with a mean an ADC value of 1.81×10 -3 mm 2 /s.…”
Section: Discussionsupporting
confidence: 86%
“…In this report, the lesions showed uniform enhancement both peripherally and centrally in the arterial phase, which persisted in the delayed phase. Either way, the enhancement pattern of MRI was similar to that of CT, with clear heterogeneous enhancement in the arterial phase and persistent hyperenhancement in the portal and delayed phases (12,14,15). In our case, the lesion showed heterogeneous septal enhancement in the arterial phase and persisted peripherally and centrally in the portal phase.…”
Section: Discussionsupporting
confidence: 74%
“…However, these findings are non-specific and will need more reporting and validation, till then it remains difficult to diagnose an AAH on the basis of imaging alone preoperatively. MRI was not performed in our case although findings provide additional impetus to the suggestion of Xue et al that possibility of AH must be kept in mind while dealing with well-circumscribed adrenal lesions demonstrating peripheral arterial enhancement 24. This finding seems more evident in larger lesions; clearly evident in our incident case, also seen in the radiological picture of the larger lesion seen in the Cleveland Clinic series.…”
Section: Discussionsupporting
confidence: 46%
“…The addition of contrast may help in visualising adrenal lesions but cannot differentiate between benign and malignant lesions 23. Application of colour Doppler has shown increased blood flow in some cases of AH 24…”
Section: Discussionmentioning
confidence: 99%